1971
DOI: 10.1136/gut.12.11.897
|View full text |Cite
|
Sign up to set email alerts
|

Antipeptic activity of antacids

Abstract: suMMARY An in vitro experiment based on the digestion of haemoglobin with pepsin was carried out to test the claim made by some manufacturers that the antacids used in their proprietary preparations had an intrinsic antipeptic activity independent of the change brought about by alteration of pH. In no case could these claims be substantiated.Antacids have played a traditional role in the treatment of peptic ulcer. Though there is no convincing proof to show that they increase the rate of healing, there is litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In 1971, an in vitro experiment by Kuruvilla revealed high anti-peptic activity (82% and 81%, respectively) for both magnesium carbonate and calcium carbonate. 61 In addition, aluminum and calcium antacids appear to adsorb pepsin and reduce its activity more strongly than would be predicted by pH changes alone. 62 Antacids such as magnesium and aluminum hydroxide can bind to bile salts, but magnesium hydroxide binds (approximately 45 mEq/h) is secreted across the apical membrane of the stomach through a proton pump (H þ /K þ ATPase) after meal consumption.…”
Section: Pepsin and Bile Acid Inhibition Activitymentioning
confidence: 98%
“…In 1971, an in vitro experiment by Kuruvilla revealed high anti-peptic activity (82% and 81%, respectively) for both magnesium carbonate and calcium carbonate. 61 In addition, aluminum and calcium antacids appear to adsorb pepsin and reduce its activity more strongly than would be predicted by pH changes alone. 62 Antacids such as magnesium and aluminum hydroxide can bind to bile salts, but magnesium hydroxide binds (approximately 45 mEq/h) is secreted across the apical membrane of the stomach through a proton pump (H þ /K þ ATPase) after meal consumption.…”
Section: Pepsin and Bile Acid Inhibition Activitymentioning
confidence: 98%
“…After administration of Rennie in our study, the activity of pepsin was reduced both within the first 5 min and over the longer term (2 h). In vitro assessment has indicated that both calcium carbonate and magnesium carbonate have high anti-peptic activity (82% and 82%, respectively) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%